Validation of FRAX® WHO Fracture Risk Assessment Tool with and without the Alara Metriscan Phalangeal Densitometer as a Screening Tool to Identify Osteoporosis in Thai Postmenopausal Women - Surakit Yingyuenyong (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective: To compare the performance of the WHO fracture risk assessment FRAX® tool and Alara Metriscan for screening osteoporosis in elderly Thai women using spine and hip BMD measurement by DXA.Materials and Methods: This study included postmenopausal Thai women, aged between 50 and 90 years, who came to check for osteoporosis at Banpho Hospital. Those met at least one of the criteria for routine axial densitometry according to the Thai Osteoporosis Foundation (TOPF) were recruited. The correlation between the FRAX® tool and Alara Metriscan, or FRAX® tool combined with Alara Metriscan classification and the actual BMD-based classification (by DXA) are summarized. Receiver operating characteristic (ROC) curves were constructed for FRAX®tool and Alara Metriscan.Results: This study included 438 postmenopausal Thai women, of whom 122 (27.9%) had osteoporosis. The mean±SD of age, body mass index were 66.4±10.6 years, 23.3±.3.5 kg/m2, respectively. The sensitivity of FRAX® and Alara Metriscan to identify osteoporosis were high (83.6% and 96.7% respectively) but the specificity (72.1%) and PPV (53.6%) of FRAX® were better. However, there is no difference in the AUCs Standard error (SE) of FRAX® (0.857(0.021)) and the AUCs (SE) of Alara metriscan (0.861(0.019)). The combination of FRAX® and Alara Metriscan had lower sensitivity (81.9%) but high specificity (79.4%) to identify women with osteoporosis. When combined FRAX® with Alara Metriscan the LR+ was 3.98 (95%CI :3.16-5.03) and LR- was 0.23 (95%CI:0.15-0.33).Conclusions: FRAX® WHO Fracture Risk Assessment Tool and Alara Metriscan may be helpful to identify women at risk of osteoporosis. Combination of both tools were significantly improve the screening of osteoporosis in postmenopausal Thai women.